2015
DOI: 10.1038/nplants.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

An intact light harvesting complex I antenna system is required for complete state transitions in Arabidopsis

Abstract: Abstract:Efficient photosynthesis depends on balancing the rate of light-driven electron transport occurring in the photosystem I (PSI) and photosystem II (PSII) reaction centers of plant chloroplast thylakoid membranes. Balance is achieved through a process called state transitions which, via redox control of the phosphorylation state of light harvesting antenna complex II (LHCII), increases its energy transfer towards PSI (State II) when PSII is overexcited, and vice versa (State I). In addition to LHCII, PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 47 publications
10
87
0
Order By: Relevance
“…In mutants defective in LHCI formation, only PSI core complexes are observed (Havaux et al, 2007;Wientjes et al, 2009;Takabayashi et al, 2011;Benson et al, 2015). A dominant band of PSI core complexes was observed in the chaos mutant (Fig.…”
Section: Accumulation Of Photosynthetic Apparatus In Ch1-2 and Cpsrp mentioning
confidence: 94%
See 4 more Smart Citations
“…In mutants defective in LHCI formation, only PSI core complexes are observed (Havaux et al, 2007;Wientjes et al, 2009;Takabayashi et al, 2011;Benson et al, 2015). A dominant band of PSI core complexes was observed in the chaos mutant (Fig.…”
Section: Accumulation Of Photosynthetic Apparatus In Ch1-2 and Cpsrp mentioning
confidence: 94%
“…1 and 2) led to further exploration of the association of LHCII with PSI or PSII during state transitions. It was recently shown that an intact LHCI complex is required for a complete state I-to-state II transition (Benson et al, 2015). To explore these findings further, we compared state transitions in ch1-2 and chaos with control seedlings.…”
Section: Impaired State Transitions In Ch1-2 and Cpsrp Mutantsmentioning
confidence: 99%
See 3 more Smart Citations